Sensory changes associated with severe ankle sprain - Bullock-Saxton, JE (Journal of rehabilitation medicine, 2020)
An intact afferent nervous system is important in providing the feedback necessary for effective motor control. Joint injury may influence afferent feedback and, if the lower limb is involved, lead to a decrease in stability. Accordingly, the association between severe ankle sprain and local sensory deficit was examined. Measurements of vibration perception, two point discrimination and balance in one legged standing were made in subjects who had sustained a previous severe unilateral ankle sprain and in subjects with no history of lower limb injury. Comparisons between the two groups showed that subjects with previous severe ankle sprain had sensory deficits in all measured variables between the injured and non-injured sides. Such differences between sides was not apparent in the non-injured group. This study highlights that local sensory deficits are associated with severe ankle sprain.